2022
DOI: 10.1038/s41467-022-33452-0
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed asymmetric allylic 4-pyridinylation via electroreductive substitution reaction

Abstract: The enantioselective pyridinylation is important for providing chiral compounds bearing heterocycles of pharmaceutical interests. 4-CN-pyrinde is extensively applied in the radical pyridinylation reaction, however, its’ enantioselective application is highly challenging. To achieve this goal, we propose an electrochemical catalytic activation of 4-CN-pyridine with a chiral transition metal complex instead of direct cathodic reduction. The chiral catalyst acts as the electron mediator and the transition metal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Therefore, paired electrolysis can be considered as the gold standard for two desirable progressions on both electrodes [ 106 , 107 ]. On the other hand, there should be more advances made in asymmetric electrochemical radical reductive transformation [ 86 , 108 ]. We hope that this Review will inspire further developments in this exciting area of electrochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, paired electrolysis can be considered as the gold standard for two desirable progressions on both electrodes [ 106 , 107 ]. On the other hand, there should be more advances made in asymmetric electrochemical radical reductive transformation [ 86 , 108 ]. We hope that this Review will inspire further developments in this exciting area of electrochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…This method was successfully applied to the synthesis of β-pyridine thioester. It should be mentioned that very recently Cheng group reported an electroreductively enantioselective Pd-catalyzed allylic 4-pyridinylation [ 86 ]. This method successfully employed the chiral η 3 allyl Pd complex to capture the persistent radical via radical rebound.…”
Section: Electrochemical Reductionmentioning
confidence: 99%
“…[150] More recently, the Cheng group described an asymmetric allyl pyridinylation of a range of allyl acetates catalyzed by electrochemistry and a chiral Pd(II)-diphosphine ligand complex to yield the corresponding allyl pyridinylation product with moderate to high levels of enantioselectivity (Scheme 47). [151] The authors suggested that the catalytic cycle commenced with the reduction of PdCl 2 -diphosphine ligand complex (L*PdCl 2 ) to the [L*Pd 0 ] active species 47A. Subsequently, Oxidative addition would happen between cinnamyl acetate 121 and 47A leading to allyl Pd II intermediate 47B, which would undergo cathodic reduction to generate Pd species 47C.…”
Section: Electro-catalyzed Decyanative Arylation Enabled By Csp3à X (...mentioning
confidence: 99%
“…In 2022, Cheng and co-workers also combined palladium catalysis with electrochemistry, developing a system in which palladium complexes act as electron mediators and transitionmetal catalysts in turn throughout the reaction (Scheme 6e). 19 4cyanopyridine was used as pyridine raw material to construct 4allyl pyridine, which represents the first case of asymmetric allyl 4-pyridylation catalyzed by 4-cyanopyridine under electrochemical conditions. Here, 4-cyanopyridine will not be directly reduced on the electrode surface, but uses palladium as an electron reduction assistant.…”
Section: Palladium Catalysismentioning
confidence: 99%